Chronic Polyhydramnios: A Medical Entity Which Could Be a Model of Muscle Development in Decreased Mechanical Loading Condition - Sekulić, Slobodan; Jakovljević, Branislava; Korovljev, Darinka; Simić, Svetlana; Čapo, Ivan; Podgorac, Jelena; Martać, Ljiljana; Kesić, Srdjan; Rakić, Srdjan; Petković, Branka (Frontiers in Physiology, 2022)
Polyhydramnios is a condition related to an excessive accumulation of amniotic fluid in the third trimester of pregnancy and it can be acute and chronic depending on the duration. Published data suggest that during muscle development, in the stage of late histochemical differentiation decreased mechanical loading cause decreased expression of myosin heavy chain (MHC) type 1 leading to slow-to-fast transition. In the case of chronic polyhydramnios, histochemical muscle differentiation could be affected as a consequence of long-lasting decreased physical loading. Most affected would be muscles which are the most active i.e. spine extensor muscles and mucles of legs. Long-lasting decreased mechanical loading on muscle should cause decreased expression of MHC type 1 leading to slow-to-fast transition, decreased number of muscle fiber type I especially in extensor muscles of spine and legs. Additionally, because MHC type 1 is present in all skeletal muscles it could lead to various degrees of hypotrophy depending on constituting a percentage of MHC type 1 in affected muscles. These changes in the case of preexisting muscle disorders have the potential to deteriorate the muscle condition additionally. Given these facts, idiopathic chronic polyhydramnios is a rare opportunity to study the influence of reduced physical loading on muscle development in the human fetus. Also, it could be a new experimental model to examine the influence of micro- and hypogravity conditions on the development of the fetal muscular system during the last trimester of gestation.